Research into the Positional Erosion around Bridges Abutments in the Garmian Region - Muhammed, Kareem Abdullah (Journal of engineering sciences and information technology, 2022)
In this research, investigation the impact of the water levels, water velocity on the drift depth of pillars of the bridges in the Garmian region was studied. The water levels and velocity were recorded for periods, different stretches between the months of December of 2018 and March of 2019. The study dealt with the most important postural relationships that can be used to estimate the depth of future drift around the pillars. Description of the site of the studying region within Garmian region includes site measurements of the bridge span, height and pillars. Hydraulic properties of the basins was studied as well as the soil texture depending on clay, silt and sand portions was detected. The depth of the site erosion did not exceed the critical limit for some pillars because it did not reach the depth of the foundation, while reach the depth of the foundation of the others pillars. The flow around the abutments of the Dardween Bridge is of a critical type, so high drifts are -+expected. The results of the gradient examination of the size of the particles in the Garmian region, shows a high proportions of the Coarse and Fine aggregates "gravel and sand" in the soil which increasing the porosity and the permeability of the soil, thus increasing the possibility of erosion at the bases of the supports for bridges in this area due to high increasing water seepage. A proposal method was obtained by the current study to estimate the erosion around bridges pillars. Using deep piles foundations for the pillar bases instead and rock dam in front of the pile foundations to reduce the impact of the flow was recommended in this study.